Conformational design concepts for anions in ionic liquids. Issue 25 (28th May 2020) - Philippi, Frederik; Pugh, David; Rauber, Daniel; Welton, Tom; Hunt, Patricia A.
Abstract : Interchangeable functional groups for imide ions are investigated computationally, new ILs with low/high viscosity are designed a priori and experimentally characterised. Abstract : The identification of specific design concepts for the in silico design of ionic liquids (ILs) has been accomplished using theoretical methods. Molecular building blocks, such as interchangeable functional groups, are used to design a priori new ILs which have subsequently been experimentally investigated. The conformational design concepts are developed by separately and systematically changing the central (imide), bridging (sulfonyl) and end (trifluoromethyl) group of the bis(trifluoromethanesulfonyl)imide [N(Tf)2 ] − anion and examining the resultant potential energy surfaces. It is shown that these design concepts can be used to tune separately the minimum energy geometry, transition state barrier height and relative stability of different conformers. The insights obtained have been used to design two novel anions for ILs, trifluoroacetyl(methylsulfonyl)imide [N(Ms)(TFA)] − and acetyl(trifluoromethanesulfonyl)imide [N(Tf)(Ac)] − . The computationally predicted structures show excellent agreement with experimental structures obtained from X-ray crystallography. [C4 C1 im][N(Tf)(Ac)] and [C4 C1 im][N(Ms)(TFA)] ILs have been synthesised and ion diffusion coefficients examined using pulsed field gradient stimulated echo NMR spectroscopy. Significantly increased diffusion was observed for the more flexible [N(Tf)(Ac)] − compared with the more rigid [N(Ms)(TFA)] − analogue. Furthermore, a pronounced impact on the fluidity was observed. The viscosity of the IL with the rigid anion was found to be twice as high as the viscosity of the IL with the flexible anion. The design concepts presented in this work will enable researchers in academia and industry to tailor anions to provide ILs with specific desired properties.